Clinical Trials: Global and Indian Context - Vennu, Vishal (India’s New Drugs and Clinical Trial Rules: Perception and Perspectives of Indian Researchers, 2021)
The concept of the clinical trial is ancient in the world, including India and the long history of clinical trials spans a wide variety of scientific, ethical, and regulatory challenges. Researchers require the most promising results from pre-clinical animal experiments to begin clinical trials on humans after the approval of the regulatory authority and ethics committee. Trials on humans are classified according to their purpose into type and phases to determine whether the new drug is safe and effective for successful treatments. The process of new drugs through phases I to IV typically takes a decade or longer and often costs well over a billion dollars. Of all drugs tested in human clinical trials, only 10% are ultimately approved by a national regulatory authority and marketed.